2017
DOI: 10.5114/jhi.2017.69169
|View full text |Cite
|
Sign up to set email alerts
|

An all-Poland survey of physical activity and sedentary lifestyles for middle school, high school and university students

Abstract: Introduction: Most countries have witnessed an increasingly sedentary lifestyle in recent decades. Experts estimate that only one third of adolescents undertake sufficient physical activity to guarantee normal physical, mental and emotional development. Study aims: To determine the frequency of PE (Physical Education) lessons as well as after-school movement activities and sedentary behaviour. To establish the association between physical activity, TV watching and computer use (screen time) with the risks of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Due to the co-existing degenerative changes of the motor system, the recommended form of exercise for the obese are 'relief exercises' (i.e. exercises in water, riding a bicycle), which do not place direct pressure on the joints of the lower limbs [42,43,44,45,46,47].…”
Section: Risks To Human Health Resulting From Low Physical Activitymentioning
confidence: 99%
“…Due to the co-existing degenerative changes of the motor system, the recommended form of exercise for the obese are 'relief exercises' (i.e. exercises in water, riding a bicycle), which do not place direct pressure on the joints of the lower limbs [42,43,44,45,46,47].…”
Section: Risks To Human Health Resulting From Low Physical Activitymentioning
confidence: 99%
“…Questionnaire results presented by Bergier et al [25] show that Eastern European adolescents have positive attitudes towards their health regarding their level of physical activity and mobility, with boys being more active than girls. As Wojtyła-Buciora et al [26] show, it is sometimes a matter of distance and time. The results of the survey show that active commuting (AC) was undertaken by 41% of middle school teenagers and 36% of high school teenagers when walking to school for up to 20 min a day, and by bicycle, only 5% and 3%, respectively.…”
Section: Influence Of Active Travel On Overall Psychical Activity And...mentioning
confidence: 99%
“…The impact of physical exercise on mental health is worth emphasizing. Regular physical activity reduces symptoms of depression and anxiety and improves mental fitness and mental well-being through an increase in blood endorphins levels [39][40][41]. Aman et al surveyed 2269 adolescents (average age 14.5 years old) from 21 paediatric diabetes departments in 19 countries.…”
Section: Physical Exercise Influence On the Organism Of Patients Withmentioning
confidence: 99%
“…In order to best support children with diabetes, experts recommend that parents, teachers, physiotherapists, and trainers should receive appropriate training on the basics of physical activity in diabetic patients [7,39,44]. Chmiel-Perzyńska et al indicated that the main source of information about diabetes among teachers is mass media.…”
Section: Recommended Dose and Types Of Physical Training For Individumentioning
confidence: 99%